Kriteria Mujtahid Perspektif Ibnu Arabi: Studi Komparasi Ijtihad Ibnu Arabi dan Para Ulama - Abshor, Ulil (PUTIH: Jurnal Pengetahuan Tentang Ilmu dan Hikmah, 2024)
The scholars have formulated the criteria for a mujtahid. And among those criteria are puberty, having an adequate understanding of sharia sources, whether the Quran or hadith, and having a set of abilities to analyze those sharia sources. However, the criteria that have been formulated are, in Ibn Arabi's view, only secondary requirements. According to him, the primary requirement that a mujtahid must have is inner readiness. Departing from this, it is necessary to explain the concept of ijtihad from the perspective of Ibn Arabi and his views in several cases of fiqh. This type of research is literature and the method used is comparative inductive while the approach used is fiqh and Sufism. As a result, ijtihad is an effort to prepare the mind, where the mujtahid must achieve the maqam of piety. And with this devotion a person will be able and ready to receive the inspirations given by Allah to him. And among the rulings that are the result of Ibn Arabi's ijtihad is the status of taklif for people who are insane, have not yet reached puberty and are asleep. According to him, the position of mukallaf in this kind of situation is "al-barâ'ah", that is, they are independent of the obligations of the Shari'ah, but nevertheless they are still subject to the status of taklif with a different essence of the taklif. And it is in the form of liberation from taklif al-ibâhah or al-barâ'ah. and so it is not lifted. However, back to human character like an animal that is just a man with a sense. This is because Ibn Arabi views that the law on an obligation is based on the value of its sharia and not based on its reason. And this has legal consequences in some cases